Pengaruh Pelayanan Pegawai Terhadap Kepuasan Pasien di Puskesmas Masalle - Junengsi; Amiruddin Tawe; Agung Widhi Kurniawan; Abdi Akbar; Uhud Darmawan Natsir (PT Maju Malaqbi Makkarana, 2023)
This study aims to determine the effect of employee service on patient satisfaction at the Masalle Health Center. The independent variable in this study is employee service, while the dependent variable is patient satisfaction. The number of patients who were sampled in this study were 40 people. The data collection techniques used were observation, questionnaires and documentation. The analysis used is descriptive analysis of percentages, simple linear regression analysis and t test. The results showed that: (1) Employee services at the Masalle Health Center, Masalle District, Masalee Regency were in the very satisfactory (very good) category. (2) Patient satisfaction at the Masalle Health Center, Masalle District, Enrekang Regency was also in the very satisfying category. (3) Employee service has a positive and significant effect on patient loyalty at the Masalle Health Center with the equation: Y = 20.050 + 0.305X. The results of this study indicate that H0 is rejected and H1 is accepted, which means that employee service has a positive and significant effect on patient satisfaction at the Masalle Health Center, Masalle District, Enrekang Regency.